Evidence for an altered architecture and a hierarchical modulation of inhibitory control processes in ADHD. (April 2019) - Chmielewski, Witold; Bluschke, Annet; Bodmer, Benjamin; Wolff, Nicole; Roessner, Veit; Beste, Christian
Abstract: Inhibitory control deficits are a hallmark in ADHD. Yet, inhibitory control includes a multitude of entities (e.g. 'inhibition of interferences' and 'action inhibition'). Examining the interplay between these kinds of inhibitory control provides insights into the architecture of inhibitory control in ADHD. Combining a Simon task and a Go/Nogo task, we assessed the interplay of 'inhibition of interferences' and 'action inhibition'. This was combined with EEG recordings, EEG data decomposition and source localization. Simon interference effects in Go trials were larger in ADHD. At the neurophysiological level, this insufficient inhibition of interferences in ADHD related to the superior parietal cortex. Simon interference effects were absent in action inhibition (Nogo) trials in ADHD, compared to controls. This was supported by bayesian statistics. The power of effects was higher than 95%. The differential effects between the groups were associated with modulations of neurophysiological response selection processes in the superior frontal gyrus. ADHD is not only associated with deficits in inhibitory control. Rather, the organization and architecture of the inhibitory control system is different in ADHD. Distinguishable inhibitory control processes operate on a hierarchical 'first come, first serve' basis and are not integrated in ADHD. This is a new facet of ADHD.